536 Intraoperative predictors of long-term pacing threshold improvement in leadless pacemakers. (8th December 2021) - Mitacchione, Gianfranco; Schiavone, Marco; Arabia, Gianmarco; Salghetti, Francesca; Cerini, Manuel; Gasperetti, Alessio; Viecca, Murizio; Curnis, Antonio; Forleo, Giovanni
Abstract: Aims: Micra-VR transcatheter pacing system (TPS) has shown strong stability of electrical parameters over time. Nevertheless, a small percentage of patients develops high pacing threshold (PT) (>1 V@0.24 ms) which can decrease the longevity of battery. Our study sought to investigate the intraoperative electrical parameters able to predict device electrical performances during the time. Methods and results: Patients (pts) implanted with Micra-VR TPS from March 2018 to January 2021 were prospectively considered at the Cardiology Department of Spedali Civili Hospital (Brescia) and Luigi Sacco Hospital (Milan). R-wave sensing amplitude (mV), pacing impedance (Ohm), and PT (V@0.24 ms) were recorded twice: upon Micra final positioning, and after removal of the delivery system. All pts received a follow-up visit at 1- and 12-month after discharge. Electrical parameters were recorded at each visit. A total of 93 pts underwent Micra-VR implantation were enrolled. When compared to the first assessment, R-wave amplitude increased of 19.1% at second control performed after 13 ± 4 min (+1.71 ± 0.2 mV, 95% CI: 1.4–2.02; P < 0.001). Conversely, PT significantly decreased of 22.1% at 12-month follow-up respect to baseline (−0.22 ± 0.03 V, 95% CI: −0.13 to − 0.31; P < 0.001) (Figure 1). Among patients with high PT, acute increase of R-wave sensing of 1.5 mV after 14 ± 4 min significantly predicted PT normalization (≤1 V@0.24 ms) 12 months post-implant ( R  = 0.72, 95% CI: 0.13–0.33, P < 0.001) (Figure 2), with a sensitivity of 87.5% (95% CI: 0.61–0.98) and a specificity of 88.8% (95% CI: 0.51–0.99) (Figure 3). Conclusions: A 1.5 mV increase in R-wave amplitude at implant time is predictive of PT normalization (<1.0 V/0.24 ms) at 12-month FU. This finding may have practical implications for device repositioning in case of HPT at implant. This parameter could be considered for acute device repositioning, particularly in HPT patients. 536 Figure